(untitled) (Research, Society and Development, 2021)
The objective of this study was to determine between different substrates which provides better conditions for vegetative propagation of ipecac via root cut, thus optimizing this process so that the limitations of the commercial scale production of the species are attenuated. An experiment was established in a greenhouse, the segments of ipecac root were introduced in trays, filled with different substrates: vermiculite, sand, coconut fiber, sawdust, rice straw and vegetable compost. The experimental design used was completely randomized with six treatments and eight repetitions, each repetition being composed of a root segment, totaling 48 experimental units. The results showed that the choice of substrate had an influence on the occurrence of shoot release. The substrates with the highest percentage of root presence were sawdust, rice straw, vermiculite and vegetable compost, respectively, followed by the substrates coconut fiber and sand. The variables number of leaves and average length of the aerial part revealed statistically similar responses between treatments, and for the variables length of root and number of root there were no significant differences. The vegetative propagation via root cut is promising when using the sawdust substrate that provides satisfactory growth, considering the mutual responses of the morphological characteristics analyzed in Psychotria ipecacuanha (Brotero) Stokes seedlings in just 10 weeks.